Exploring the relationships between self-efficacy, self-care, and glycaemic control in primary care diabetes management - Le Ho Thi Quynh Anh; Nguyen Vu Quoc Huy; Nguyen Minh Tam; Johan Wens; Anselme Derese; Wim Peersman; Vo Ngoc Ha My; Tran Binh Thang; Nguyen Thi Phuong Anh; Tran Thi Truc Ly; Peter Pype (SAGE Open Medicine)
Objectives: Our study aimed to identify the complex interplay between self-efficacy, self-care practice, and glycaemic control among people with type 2 diabetes mellitus (PWDs) to inform the design of more targeted and effective behavioural interventions in primary care. Methods: A cross-sectional descriptive study was performed with 294 PWDs managed in primary care. The Diabetes Management Self-Efficacy Scale (DMSES) and Summary of Diabetes Self-Care Activities (SDSCA) questionnaire measured patients’ self-efficacy and self-care practice. Multivariate logistic regression models were developed to explore how SDSCA, DMSES, and their combined effect relate to glycaemic control, adjusting for patient characteristics. Network analysis in R software examined relationships between self-efficacy and self-care dimensions across glycaemic control subgroups using a Gaussian graphical model with the extended Bayesian information criterion. Results: Half the PWDs (50.7%) had suboptimal glycaemic control. Better glycaemic control was consistently associated with higher self-efficacy (odds ratio (OR) = 0.76, 95% confidence (CI) (0.60, 0.97), p  = 0.03), shorter duration of diabetes (OR = 1.89, 95% CI (1.08, 3.31), p  = 0.03), normal waist circumference (OR = 1.76, 95% CI (1.02, 3.05), p  = 0.04), absence of diabetes complications (OR = 2.09, 95% CI (1.10, 3.98), p  = 0.02), and treatment with oral hypoglycaemic agents (OR = 3.05, 95% CI (1.53, 6.09), p  < 0.01). Network analysis among people with well-controlled HbA1c revealed that diet adherence and self-efficacy had the most robust connection, with diet self-efficacy strongly associated with most self-efficacy dimensions. Self-efficacy in exercise, blood glucose monitoring, and foot care are the most central factors in the network structures for PWDs with suboptimal glycaemic control. Conclusions: Our study highlights the critical role of self-efficacy in diabetes primary care. For people with optimal glycaemic control, prioritising self-efficacy in diet adherence is crucial for sustaining glycaemic outcomes and supporting other self-care behaviours. Among those with suboptimal glycaemic control, enhancing self-efficacy in exercise, blood glucose monitoring, and foot care is essential. Targeted education programs, personalised counselling, and E-health tools can further empower patients to manage their diabetes more effectively.